A differential game of evasion from many pursuers - Ibragimov, G. I.; Mat Hasim, Risman (Universiti Putra Malaysia Press, 2008)
This paper considers a game problem with many pursuers described by infinite systems of differential equations of second order. On the controls of players geometric constraints are imposed. The aim of the pursuers is to capture the evader,while the aim of the evader is the opposite. The theorem on evasion is proved in this paper.